Hepatitis B inactive carriers: An overlooked population? - Pita,Inês (2014)
A significant portion of chronic hepatitis B (HBV) infected patients is in the inactive carrier state, characterized by normal transaminase levels, little viral replication and minimal liver necroinflammatory activity. Diagnosis is made after at least one year of regular monitoring and requires lifelong follow-up to confirm that this state is maintained. Studying the natural history of inactive carriers is currently hindered by the small number of studies on patients correctly diagnosed according to current guidelines. When correctly defined, inactive carrier state carries a very good prognosis in the spectrum of chronic hepatitis B infection, with low rates of reactivation, hepatocellular carcinoma and progression of disease to cirrhosis. In addition, clearance of hepatitis B surface antigen is more common in inactive carriers compared to the general HBV infected population. Reactivation is more likely during the first years of follow-up and during immunosuppressive therapies. Prophylactic antiviral treatment should be initiated as soon as possible in this latter case. Current guidelines do not routinely recommend liver biopsy in inactive carriers. However, some may have significant hepatic fibrosis at diagnosis and cannot therefore be classified as such; others may develop fibrosis during follow-up and consequentially have poorer prognosis. Despite some limitations, transient elastography appears an ideal approach for identifying such patients and for serial monitoring of liver changes in all inactive carriers. Overall, more longitudinal studies on larger cohorts of true inactive carriers would be helpful for establishing with greater certainty the most appropriate management strategy in these patients.